2022
DOI: 10.1128/spectrum.01230-22
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate Kinase Is Required for the Processes of Virulence and Persistence in Acinetobacter baumannii

Abstract: A. baumannii was identified as a top-priority pathogen by the WHO due to its antibiotic resistance. Meanwhile, the pathogenicity of A. baumannii mediated by several vital virulence factors also cannot be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
4
8
0
Order By: Relevance
“…The Δ ppk1 and Δ ppk1 -Δ ppx mutants exhibited reduced biofilm formation compared to the WT strain. These results are consistent with previous reports in various models 28,6669 . Interestingly, the use of mesalamine, a drug used in the treatment of ulcerative colitis that also inhibits PPK1 30 , showed similar levels of biomass reduction in the biofilm as observed in Δ ppk1 and Δ ppk1 -Δ ppx mutant cells, confirming the close association between biofilm formation and polyphosphates.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The Δ ppk1 and Δ ppk1 -Δ ppx mutants exhibited reduced biofilm formation compared to the WT strain. These results are consistent with previous reports in various models 28,6669 . Interestingly, the use of mesalamine, a drug used in the treatment of ulcerative colitis that also inhibits PPK1 30 , showed similar levels of biomass reduction in the biofilm as observed in Δ ppk1 and Δ ppk1 -Δ ppx mutant cells, confirming the close association between biofilm formation and polyphosphates.…”
Section: Discussionsupporting
confidence: 94%
“…S2B). PPK1 is the main enzyme responsible for synthesizing polyP in bacterial models such as P. aeruginosa and Acinetobacter baumannii 23,28 . However, its role in K. pneumoniae has not been extensively studied.…”
Section: Deleting Polyp Metabolism Genes Does Not Affect Viability An...mentioning
confidence: 99%
“…PPK1 is the main enzyme responsible for synthesizing polyP in bacterial models such as P. aeruginosa and Acinetobacter baumannii. , However, its role in K. pneumoniae has not been extensively studied.…”
Section: Resultsmentioning
confidence: 99%
“…PPK1 is the main enzyme responsible for synthesizing polyP in bacterial models such as P. aeruginosa and Acinetobacter baumannii. 24,28 However, its role in K. pneumoniae has not been extensively studied. Nutrient deprivation is a known condition that promotes the accumulation of polyP in bacteria.…”
Section: Mutants Lacking Genes Involved In Polyp Synthesis and Degrad...mentioning
confidence: 99%
“…In other pathogenic bacteria, it has been suggested that the production of storage compounds affects virulence. This, together with the increased ROS sensitivity of the Δwax/dgat::kanR mutant, prompted us to analyze the effect of the absence of WS/DGAT on the survival of Galleria mellonella . Therefore, we grew the A. baumannii wild type and the Δwax/dgat::kanR mutant in the presence or absence of nitrogen limitation and used these cultures to infect G. mellonella .…”
Section: Resultsmentioning
confidence: 99%